2018
DOI: 10.1161/jaha.117.008363
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Responses to Altered Sodium Intake in Rat Pregnancy

Abstract: BackgroundIn pregnancy, a high plasma volume maintains uteroplacental perfusion and prevents placental ischemia, a condition linked to elevated maternal blood pressure (BP). Reducing BP by increasing Na+ intake via plasma volume expansion appears contra‐intuitive. We hypothesize that an appropriate Na+ intake in pregnancy reduces maternal BP and adapts the renin‐angiotensin system in a pregnancy‐specific manner.Methods and Results BP was measured by implanted telemetry in Sprague‐Dawley rats before and through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…Non‐significant fluctuations in the spot U[Na + ]/[Cr] ratios throughout the pregnancies and a weak negative correlation with BPs were found in our study, similar to the findings of a prospective cohort study from the Netherlands 21 . In an animal study, a high salt intake in pregnant rats was associated with lower nighttime BP 22 . These findings may be because sodium is retained by post‐translational activation of sodium transport and previous high salt intake bridging a consecutive period of low salt intake by maintaining a lower BP 23 .…”
Section: Discussionsupporting
confidence: 89%
“…Non‐significant fluctuations in the spot U[Na + ]/[Cr] ratios throughout the pregnancies and a weak negative correlation with BPs were found in our study, similar to the findings of a prospective cohort study from the Netherlands 21 . In an animal study, a high salt intake in pregnant rats was associated with lower nighttime BP 22 . These findings may be because sodium is retained by post‐translational activation of sodium transport and previous high salt intake bridging a consecutive period of low salt intake by maintaining a lower BP 23 .…”
Section: Discussionsupporting
confidence: 89%
“…In general, 3 g to 5 g of daily sodium intake is recommended [204]. Previous works have evidenced that high-salt diets (more than 5 g of sodium per day) have detrimental effects on the placenta, altering its metabolism, function, inflammation, hypoxia, and other pathogenic processes [205,206]. Beauséjour et al [207] also observed that pregnant Sprague-Dawley rats experienced a significant augmentation in oxidative stress markers in the placenta under increased sodium intake.…”
Section: Role Of Westernized and Unhealthy Dietary Patterns In The Pl...mentioning
confidence: 99%